1998
DOI: 10.1097/00043426-199803000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Donor Lymphocyte Infusions to Displace Residual Host Hematopoietic Cells after Allogeneic Bone Marrow Transplantation for β-Thalassemia Major

Abstract: This case report shows that DLI can effectively eradicate host stem cells in mixed chimeras after BMT in nonmalignant hematopoietic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
41
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 12 publications
0
41
0
Order By: Relevance
“…21 The use of donor leukocyte infusions should be carefully considered in patients with stable chimerism since the treatment may be associated with significant risks. 22 In conclusion, BMT for Chinese TM patients has a similar outcome as for Caucasian patients. Older age is associated with treatment failure, and transplantation should be performed early if HLA-identical siblings are available.…”
Section: Discussionmentioning
confidence: 78%
“…21 The use of donor leukocyte infusions should be carefully considered in patients with stable chimerism since the treatment may be associated with significant risks. 22 In conclusion, BMT for Chinese TM patients has a similar outcome as for Caucasian patients. Older age is associated with treatment failure, and transplantation should be performed early if HLA-identical siblings are available.…”
Section: Discussionmentioning
confidence: 78%
“…21,[29][30][31] The rationale here is that transient maximal immunosuppression achieved by non-myeloablative agents such as Flu and ATG suffices to ensure stable engraftment with partial, if not complete, chimerism and a state of bilateral tolerance. 21 Once this state is achieved, donor alloreactive T cells may be used against residual malignant or genetically abnormal stem cells in order to achieve complete chimerism [22][23][24] without megadoses of chemoradiotherapy. DLI has previously been shown by us to convert partial chimerism to full donor chimerism in children with genetic disease, [22][23][24] and may also be suitable for increasing engraftment of genetically engineered cells following gene therapy, which has recently been attempted in CGD.…”
Section: Discussionmentioning
confidence: 99%
“…21 Once this state is achieved, donor alloreactive T cells may be used against residual malignant or genetically abnormal stem cells in order to achieve complete chimerism [22][23][24] without megadoses of chemoradiotherapy. DLI has previously been shown by us to convert partial chimerism to full donor chimerism in children with genetic disease, [22][23][24] and may also be suitable for increasing engraftment of genetically engineered cells following gene therapy, which has recently been attempted in CGD. 6,32 This approach is especially suitable for children with genetic diseases, where it has been demonstrated that agents with adequate anti-lymphoid and anti-hematopoietic stem cell activity are necessary in order to achieve complete donor lymphoid and hematopoietic stem cell engraftment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Although donor lymphocyte infusion (DLI) is an effective treatment for late recurrence of some hematological malignancies after allogeneic BMT, 6 DLI has only been reported in few cases for early graft failure in thalassemia. 7,8 We report a case of late recurrent b-thalassemia major successfully treated with DLI 23 years after BMT. The patient signed institutional review board-approved consent to allow his medical records to be used for research.…”
mentioning
confidence: 99%